Download presentation

Presentation is loading. Please wait.

Published byMartina Underwood Modified over 6 years ago

3
Graphing Systems of Equations Graph of a System Intersecting lines- intersect at one point One solution Same Line- always are on top of each other, slope is equal. Infinitely many solutions Parallel lines- are opposite from each other and will never! intersect. No solution

4
Example 1-Number of solutions Y=-x+5 Y=x-3 Since the graph of y=-x=5 and y=x-3 are intersecting lines there is one solution. Example 2-Solve a System of Equations Y=-x+8 y=4x-7 the graph appears to intersect at the point with coordinates (3,5). Check the estimate by replacing x with 3 and 5 with y in both equations.

5
Substitution Example 1-Solve using Substitution Y=3x X+2y=-21 Since y =3x, substitute 3x for y in the second equation. X+2y=-21 2 nd equation X+2(3x)=-21 y=3x x+6x=-21 simplify 7x=-21 combine like terms 7x/7=-21/7 divide each side by 7 X=-3 Use y=3x to find the value of y. y=3x y=-9 Y=3(-3) The solution is ( -3,-9)

6
Elimination Using Addition and Subtraction Example 1-Elimination using Addition 3x-5y=-16 2x+5y=31 Since the coefficients of the y terms,-5 and 5, are additive inverse, you can eliminate the y terms by adding the equations. 3x-5y=-16 +2x+5y=31 Notice the y variable is eliminated. 5x = 15 5 5 divide each side by 5 x=3 simplify

7
Example 1-Continued Now substitute 3 for x in either equation to find the value of y. 3x-5y=-16 first equation 3(3)-5y=-16 replace x with 3 9-5y=-16 simplify -9 -9 subtract 9 from each side -5y=-25 simplify -5 -5 divide each side by -5 Y=5 The solution is (3, 5)

8
Example 2-Elimination Using Subtraction 5s+2t=6 9s+2t=22 Since the coefficients of the t terms, 2 and 2, are the same you can eliminate them by using subtraction. 5s+2t=6 (-)9s+2t=22 Notice that the variable t is eliminated. -4s -16 -4 -4 Divide each side by -4 S=4 Simplify

9
Example 2- Continued Now substitute 4 for s in either equation to find the value of y. 5s+2t=6 5(4)=2t=6 Replace s with 4 20 +2t=6 Simplify -20 -20 Subtract 20 from each side 2t=-14 Simplify 2 2 Divide each side by 2 t=-7 The solution is (4, -7)

10
Elimination Using Multiplication Example 1-Multiply one Equation to Eliminate 3x+4y=6 5x+2y=-4 Multiply the 2 nd equation by -2 so the coefficients of the y terms are additive inverse. Then add the equations. 3x+4y=6 5x+2y=-4 (+)-10x-4y=8 Mult by 2 -7x 14 Add the equations -7 -7 Divide each side by -7 x=-2

11
Example 1- Continued Now substitute -2 for x in either equation. 3x+4y=6 3(-2)+4y=6 x=-2 -6+4y=6 Simplify +6 +6 add 6 to both sides 4y=12 Simplify 4 4 Divide by 4 on each side y=3 The solution is (-2, 3)

Similar presentations

© 2021 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google